DNA Methylation in Schizophrenia Subjects: Gender and MTHFR 677C/T Genotype Differences - Burghardt, Kyle J; Pilsner, J Richard; Bly, Michael J; Ellingrod, Vicki L (Epigenomics, 2012)
In schizophrenia, metabolic syndrome incidence is double that of the general population, with women having a higher incidence. Pharmacogenetically regulated folic acid may be related to this risk. DNA methylation and metabolic syndrome within this group has not been previously studied. Metabolic syndrome was evaluated with fasting laboratory measurements, and dietary and lifestyle assessments. Methylation analysis used a peripheral sample for the LINE-1 assay. DNA was also genotyped for MTHFR 677C/T. This analysis included 133 subjects. We found a significant relationship between LINE-1 methylation, and an interaction between MTHFR and gender, controlling for serum folate (p = 0.008). Females with the 677TT genotype had the lowest methylation (56%) compared with the other groups (75%). TT genotype females had the lowest methylation, which may explain metabolic syndrome gender differences in schizophrenia. Folate supplementation may be a suggested intervention within schizophrenia; however, additional work is required.